2019
DOI: 10.1093/tas/txz176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lipid matrix microencapsulation for intestinal delivery of thymol in weaned pigs

Abstract: Essential oils (EO) are defined as plant-derived natural bioactive compounds, which can have positive effects on animal growth and health due to their antimicrobial and antioxidative properties. However, EO are volatile, can evaporate quickly, and be rapidly absorbed in the upper gastrointestinal tract. Also, due to their labile nature, the stability of EO during feed processing is often questionable, leading to variations in the final concentration in feed. Encapsulation has become one of the most popular met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…In fact, EO may increase the permeability of cell membranes which allows organic acids to diffuse easily into the microbial cells. Recently, microencapsulation of organic acids and EO has shown to prevent their absorption in the upper part of digestive tract, while allowing a higher bioactivity towards the lower gastrointestinal tract [19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, EO may increase the permeability of cell membranes which allows organic acids to diffuse easily into the microbial cells. Recently, microencapsulation of organic acids and EO has shown to prevent their absorption in the upper part of digestive tract, while allowing a higher bioactivity towards the lower gastrointestinal tract [19].…”
Section: Introductionmentioning
confidence: 99%
“…Organic acids and EO are volatile and can evaporate quickly during feed processing or being absorbed in the stomach and proximal small intestine ( Michiels et al, 2008 ). Microencapsulation is a feasible strategy to be used to, among other advantages, improve stability and protect feed additives during processing, reduce the effective dose, delay the absorption of these molecules and to be slowly released throughout the intestine of the animals ( Choi et al, 2020 ). For instance, Choi et al (2020) showed that 15.5% of microencapsulated thymol was released in the stomach, 41.85% was released in the mid-jejunum section, and 2.21% was recovered in the feces, showing that lipid matrix microparticles can maintain the stability of thymol and allowed a progressive release of thymol in the intestine of pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation is a feasible strategy to be used to, among other advantages, improve stability and protect feed additives during processing, reduce the effective dose, delay the absorption of these molecules and to be slowly released throughout the intestine of the animals ( Choi et al, 2020 ). For instance, Choi et al (2020) showed that 15.5% of microencapsulated thymol was released in the stomach, 41.85% was released in the mid-jejunum section, and 2.21% was recovered in the feces, showing that lipid matrix microparticles can maintain the stability of thymol and allowed a progressive release of thymol in the intestine of pigs. Therefore, microencapsulated OA and EO may have more influence on the distal portions of the GIT when compared to non-encapsulated molecules which may be essential to prevent pathogen proliferation in the lower parts of the intestine, where higher bacterial concentration is found.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of the MPs was not demonstrated. The intestinal delivery of thymol has also been assessed when microencapsulated into commercial lipid matrices containing organic acids by Choi et al ( 2020 ), demonstrating the stability of the systems during feed pelleting and storing processes and an in vitro and in vivo sustained release of thymol in simulated gastric and intestinal fluids and pig guts, respectively (Choi et al, 2020 ).…”
Section: Oeo Microencapsulationmentioning
confidence: 99%